PENGEMBANGAN MEDIA VIDEO TARI UNTUK MENSTIMULASI PERKEMBANGAN SENI DAN FISIK MOTORIK DI TAMAN KANAK-KANAK - Danang Prastyo; Yesi Novitasari (JCE (Journal of Childhood Education), 2020)
Early childhood learning process must prioritize children's development can not only be seen from the results. Therefore real experiences and facilities in learning must be interesting and can be digested as well as possible by children in order to get optimal results. The ability to do dance movements is important for children because through dance movements children can express themselves into movements that have meaning that also help the development of children's art and physical motor skills. This study aims to determine the feasibility and effectiveness of dance video media in stimulating the development of motor and physical art in kindergarten children.This research is a development research. The research instruments used were observation, questionnaires and interview guides. The data analysis technique used in this study was paired sample t-test. And processing data using Spss 20. The results in this study indicate that: (1) The use of dance video media is appropriate to stimulate the development of art and physical motor skills of a kindergarten child; (2) The use of dance video media is effective in stimulating the art and physical development of kindergarten children